Unveiling physiological responses and modulated accumulation patterns of specialized metabolites in Mentha rotundifolia acclimated to sub-tropical environment - Chatterjee, Dipanjali; Mitra, Adinpunya (Physiology and molecular biology of plants, 2024)
Mints are aromatic plants of Lamiaceae , globally known for the phytochemical-rich essential oils. Most of the cultivated mints are menthol-rich, whereas spearmint being the only dominant carvone-rich species. In this study, another carvone-rich mint Mentha rotundifolia (L.) Huds., a native of temperate region was assessed for its acclimation in sub-tropical environment to see any possible changes in specialized metabolite accumulation. Plants grown under open environment was compared with glasshouse grown plants where, temperature, humidity and photoperiods were uniformly maintained. Thickened leaves with increased cuticular wax load (2.82 folds) and anthocyanin accumulation (202.97 µg/g) in the widened stems were observed in plants grown in open environment, while higher chlorophyll contents were exhibited by the glasshouse-grown plants. Enhanced antioxidant capacity in open environment, correlated with elevated concentration (86.4% increase for caffeic acid) of wall-bound phenolics was observed. Increased proline, hydrogen peroxide and malondialdehyde contents in open environment indicated the plant’s ability to cope up with abiotic stress. Higher amounts of terpenes like (-)-carvone (2.68 folds) and D-limonene (1.35 folds) were found in both internal volatile pool and essential oil of glasshouse-grown plants. Histochemical study of glandular trichomes also supported this finding. In conclusion, glasshouse-grown plants showed relatively better growth and higher terpene contents, nevertheless the plant survived well in warmer environment, with increased antioxidant capacities and phenolic contents. Future study includes mass propagation of this species in different geographical locations with distinct climatic variations to determine the suitable sub-tropical locations for cultivation as a potential alternative to spearmint for commercial-scale (-)-carvone production.